SYNTHESIS OF POROUS CARBON MATERIAL PROPYLENE MEDICAL MASK AS ADSORBENT HEAVY METAL IRON (Fe) IN WATER EX-TIN MINING BANGKA BELITUNG - Amelia, Addela; Putri, Faizah Alivia; Widia; Adelia, Della; Alkasiyah; Fabiani, Verry Andre (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2024)
Bangka Belitung Islands Province faces severe environmental challenges, exacerbated byillegal tin mining activities leading to heightened pollution levels, particularly in stagnantwater within former tin mining holes, reaching depths of up to 40 meters. The presence ofiron metal (Fe) in this water poses a health risk, potentially damaging intestinal walls andcompromising lung function upon ingestion. This study presents a novel approach to addressthis issue by synthesizing porous carbon material from propylene waste sourced frommedical masks. The process involves initial sulfonation for sterilization and pore sizeenhancement, followed by activation using KOH and carbonization at 750 °C.Characterization methods validate the successful synthesis, including FTIR highlightingpolypropylene groups at 822 cm-1, XRD indicating graphite carbon with high crystallinity,and SEM exhibiting rod shapes and cavities at 5,000í— magnification. The adsorption testdemonstrates outstanding performance, with porous carbon exhibiting a 100% adsorptionefficiency in purifying water, eliminating odors, and reducing iron (Fe) levels. Thisinnovative method effectively reduces iron levels in stagnant water environments, providinga sustainable solution to environmental pollution, particularly in Bangka Belitung.